b multi-professional approach for healthcare practitioners /c - Keeling, June.; Mason, Tom. (b, 2009)
"This book takes a multi-agency approach to domestic violence and looks at a large range of issues that impact on those working in the health and social care field"--EBL
Includes bibliographical references and index.
Keywords: Family violence -- Prevention. -- Great Britain; Victims of family violence -- Services for -- Great Britain